2016
DOI: 10.14520/adyusbd.70805
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen Adaylarinin Öz-Yeterli̇k Algilari

Abstract: Öz

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
3
0
6
Order By: Relevance
“…Similarly, there are also studies indicating that men have higher academic self-efficacy levels than women (Durdukoca, 2010;Vurucu, 2010). However, there are also studies in the literature that did not find significant differences between male and female students (Doğaner, 2017;Kavrayıcı & Bayrak, 2016;Kılıç & Öncü, 2014;Özsüer, 2011;Uysal, 2013;Ünlü & Kalemoğlu, 2011;Yaşartürk et al, 2018). This shows that the studies in the literature show different results and that the female students in our sample group had higher self-confidence in their courses or academic studies, and it can be concluded that women, in the social conditions they live in, are more effective than males in learning and in applying their acquisitions in real life in terms of the social dimension.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, there are also studies indicating that men have higher academic self-efficacy levels than women (Durdukoca, 2010;Vurucu, 2010). However, there are also studies in the literature that did not find significant differences between male and female students (Doğaner, 2017;Kavrayıcı & Bayrak, 2016;Kılıç & Öncü, 2014;Özsüer, 2011;Uysal, 2013;Ünlü & Kalemoğlu, 2011;Yaşartürk et al, 2018). This shows that the studies in the literature show different results and that the female students in our sample group had higher self-confidence in their courses or academic studies, and it can be concluded that women, in the social conditions they live in, are more effective than males in learning and in applying their acquisitions in real life in terms of the social dimension.…”
Section: Discussionmentioning
confidence: 98%
“…Motivasyonun, eğitim başarısını belirlemede kritik faktörlerden biri olduğu ifade edilmekte (Ryan ve Deci, 2000) hatta öğrencilerin öğrenmesinde, öğretmenlerin motivasyonunun mesleki Yaz/Summer(2019) -Cilt/Volume:18 -Sayı/Issue:71 (0000000) yeterliliklerinden daha etkili bir değişken olduğunu yapılan bir araştırma ortaya koymaktadır (Atkinson, 2000).…”
Section: Introductionunclassified
“…Thus, it could be stated that the department variable does not influence academic self-efficacy belief. There are studies the results of which overlap with this study (Çubukçu & Girmen, 2007;Demir, 2013;Elkatmış, Demirbaş & Ertugrul, 2013;Eroğlu, Yıldırım & Şahan, 2017;Güven & Baltaoğlu,2017;Kavrayıcı & Bayrak, 2016;Oğuz, 2009;Saracaloğlu, Yenice & Özden, 2013;Uysal & Kösemen, 2013). Eroğlu, Yıldırım and Şahan (2017) found in their study that there was no significant difference between the self-efficacy levels of students studying in the Faculty of Physical Education in terms of department variable.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 46%
“…Bu durumda bölüm değişkeninin akademik öz yeterlik algısı üzerinde etkili olmadığı söylenebilir. Bu araştırma bulgusu ile paralellik gösteren araştırmalar (Çubukçu & Girmen, 2007;Demir, 2013;Elkatmış, Demirbaş & Ertuğrul, 2013;Eroğlu, Yıldırım & Şahan, 2017;Güven & Baltaoğlu,2017;Kavrayıcı & Bayrak, 2016;Oğuz, 2009;Saracaloğlu, Yenice & Özden, 2013;Uysal & Kösemen, 2013) bulunmaktadır. Eroğlu, Yıldırım ve Şahan (2017), araştırmalarında spor bilimleri fakültesi öğrencilerinin akademik öz yeterlik düzeylerinin bölüm değişkenine göre istatistiksel olarak anlamlı bir farklılık göstermediğini tespit etmişlerdir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified